RNA‐Seq detects a SAMD12‐EXT1 fusion transcript and leads to the discovery of an EXT1 deletion in a child with multiple osteochondromas. Issue 3 (10th January 2019) - Oliver, Gavin R.; Blackburn, Patrick R.; Ellingson, Marissa S.; Conboy, Erin; Pinto e Vairo, Filippo; Webley, Matthew; Thorland, Erik; Ferber, Matthew; Van Hul, Els; van der Werf, Ilse M.; Wuyts, Wim; Babovic‐Vuksanovic, Dusica; et al.
Abstract: Background: We describe a patient presenting with pachygyria, epilepsy, developmental delay, short stature, failure to thrive, facial dysmorphisms, and multiple osteochondromas. Methods: The patient underwent extensive genetic testing and analysis in an attempt to diagnose the cause of his condition. Clinical testing included metaphase karyotyping, array comparative genomic hybridization, direct sequencing and multiplex ligation‐dependent probe amplification and trio‐based exome sequencing. Subsequently, research‐based whole transcriptome sequencing was conducted to determine whether it might shed light on the undiagnosed phenotype. Results: Clinical exome sequencing of patient and parent samples revealed a maternally inherited splice‐site variant in the doublecortin ( DCX ) gene that was classified as likely pathogenic and diagnostic of the patient's neurological phenotype. Clinical array comparative genome hybridization analysis revealed a 16p13.3 deletion that could not be linked to the patient phenotype based on affected genes. Further clinical testing to determine the cause of the patient's multiple osteochondromas was unrevealing despite extensive profiling of the most likely causative genes, EXT1 and EXT2, including mutation screening by direct sequence analysis and multiplex ligation‐dependent probe amplification. Whole transcriptome sequencing identified a SAMD12‐EXT1 fusion transcript that could have resulted from a chromosomal deletion, leading to the loss of EXT1 function. Re‐review of the clinical array comparative genomic hybridization results indicated a possible unreported mosaic deletion affecting the SAMD12 and EXT1 genes that corresponded precisely to the introns predicted to be affected by a fusion‐causing deletion. The existence of the mosaic deletion was subsequently confirmed clinically by an increased density copy number array and orthogonal methodologies Conclusions: While mosaic mutations and deletions of EXT1 and EXT2 have been reported in the context of multiple osteochondromas, to our knowledge, this is the first time that transcriptomics technologies have been used to diagnose a patient via fusion transcript analysis in the congenital disease setting. Abstract : We describe the identification of a diagnostic EXT1 gene fusion in a patient with multiple osteochondromas following extensive negative clinical testing. Follow up reanalysis of clinical results revealed an underlying mosaic chromosomal deletion. The article reveals shortcomings in clinical testing and is the first report of a gene fusion diagnostic of multiple osteochondromas.